Beyond Bancor. Issue 1 (2nd January 2016) - Mehrling, Perry
Abstract : Economists today rely on the Bancor discussion, largely initiated by John Maynard Keynes at Bretton Woods, to criticize the International Monetary Fund's latest prescriptions. But the argument is out-of-date.